Ultrasenzitivne merený C-reaktivní protein--nový parametr kardiovaskulárního rizika - Dvoráková, A; Poledne, R (Vnitrni lekarstvi, 2004)
Elevated C-reactive protein concentration, measured by an ultrasensitive method (hsCRP), has been proved to be a risk factor for atherosclerosis progression and its complications (myocardial infarction and stroke) in otherwise healthy men and women. In patients with already diagnosed atherosclerotic disease elevated concentration of hsCRP predicts prognosis. There are multiple causes of elevated hsCRP concentration: metabolic changes (e.g. as a part of metabolic syndrome), genetic background and chronic infections. Proinflammatory effect of adipose tissue in obese individuals seems to play an important role, hsCRP levels correlate with markers of abdominal obesity. Elevated hsCRP concentrations can be lowered both pharmacologically and by a lifestyle change. This review covers current knowledge of pathophysiology of elevated hsCRP concentration and possible use of this method in clinical medicine.
Keywords: Arteriosclerosis; biologické markery; metabolický syndrom; lidé; nefelometrie a turbidimetrie; C-Reactive Protein; Metabolic Syndrome; Nephelometry and Turbidimetry; Cardiovascular Diseases; rizikové faktory; Immunoassay; Biomarkers; Humans; imunoanalýza; Risk Factors; kardiovaskulární nemoci; arterioskleróza; C-reaktivní protein